2012
DOI: 10.1186/ar3899
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 2 cross-linking activity is linked to invadopodia formation and cartilage breakdown in arthritis

Abstract: IntroductionThe microenvironment surrounding inflamed synovium leads to the activation of fibroblast-like synoviocytes (FLSs), which are important contributors to cartilage destruction in rheumatoid arthritic (RA) joints. Transglutaminase 2 (TG2), an enzyme involved in extracellular matrix (ECM) cross-linking and remodeling, is activated by inflammatory signals. This study was undertaken to assess the potential contribution of TG2 to FLS-induced cartilage degradation.MethodsTransglutaminase (TGase) activity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 64 publications
1
35
0
Order By: Relevance
“…Interestingly, TNF resistance has recently been associated with a distinct synovial fibroid phenotype enriched for gene sets associated with TGF-b/SMAD signaling, as well as cell projection processes (95). In this work, we show that blockade of the TbR1/PDGFR axis or downstream PI3K-AKT pathway impaired invadosome formation, a process previously linked to cartilage damage (5,6). Various small-molecule inhibitors of TGF-b are being evaluated in preclinical and clinical trials (96).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Interestingly, TNF resistance has recently been associated with a distinct synovial fibroid phenotype enriched for gene sets associated with TGF-b/SMAD signaling, as well as cell projection processes (95). In this work, we show that blockade of the TbR1/PDGFR axis or downstream PI3K-AKT pathway impaired invadosome formation, a process previously linked to cartilage damage (5,6). Various small-molecule inhibitors of TGF-b are being evaluated in preclinical and clinical trials (96).…”
Section: Discussionmentioning
confidence: 85%
“…They were shown to contain actin components, signaling molecules, such as Src, and high levels of proteolytic enzymes known to be particularly efficient at inducing cartilage damage. Importantly, interference with the formation of invadosomes in arthritic FLS strongly inhibited matrix degradation in vitro and ex vivo as well as cartilage degradation in a rat model of arthritis (5,6). These observations suggested that invadosomes were directly involved in joint degradation, leading to the conclusion that an in-depth understanding of the mechanism of invadosome formation is of importance for development of joint protection strategies for the clinical management of RA.…”
mentioning
confidence: 88%
See 3 more Smart Citations